Measurement of water concentration along the straight channel of proton exchange membrane fuel cell. (28th February 2022) - Han, Jaesu; Kim, Younghyeon; Kim, Taehyeong; Yu, Sangseok
Highlights: Reliability tests of a T/RH sensor were performed in an environment similar to that of a PEMFC. Experiments were conducted to investigate the effects of heat and water in PEMFC. Temperature and humidity data showed the important clues to predict water transport through a membrane. Conversion of the dew point temperature shows the product water is transported from the cathode to the anode. Abstract: Given that the ionic conductivity of a proton exchange membrane fuel cell is significantly influenced by water concentration in the channel, an elaborate water management strategy is crucial to ensure durability and performance of these types of fuel cells. In this study, the vapour concentration of a gas mixture was observed in the through-plane direction in a bipolar plate. The stainless steel bipolar plate used here has straight channels containing installed relative humidity/temperature micro-sensors such that the vapour flow behaviour can be observed. The vapour concentration in the anode channel is increased by the back diffusion of water vapour from the cathode. The vapour concentration at the cathode channel increases with the water produced during the electrochemical reaction. The distribution of the dew point temperature at the anode/cathode channel shows that water transport to the anode increases the vapour concentration of anode gases.